Side event, Bonn, Germany 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS') side event on how agriculture could contribute to adaptation and mitigation. Held during the Subsidiary Body for Scientific and Technological Advice (SBSTA) in Bonn, Germany. Panel included: Manyewu Mutamba (SACAU), Sonja Vermeulen (CCAFS), James Kinyangi (CCAFS), Henry Neufeldt (ICRAF) and Mohammed Asaduzzaman VIce-Chair Commission on Sustainable Agriculture and Climate Change). Photo: C. Schubert (CCAFS).